The relationship between childhood attachment, parenting styles and social development in autism spectrum disorder - Carter, Kirsty (Department of Psychology, 2020)
Although social deficits are a defining feature in Autism Spectrum Disorder (ASD), not enough is known about the origin and impact of these impairments. Current research agrees that deficits in Theory of Mind (ToM) contribute to the social disconnectedness evident in children with ASD. Furthermore, studies in neurotypical populations have found significant links between attachment security and ToM acquisition, and some have posited parenting behaviours as predictors of social development. Less is known about these construct in children with ASD. This study aimed to form a foundational view of the relationships between parenting style, attachment, and Theory of Mind development in a sample of ASD children compared to a sample of neurotypical children. 80 parent-child pairs were included in the study. The sample was comprised of 40 verbal children with an ASD diagnosis and 40 neurotypical children. Children between the ages of 6 and 16 years were included in the study. Parenting style and attachment were measured using scaled response parent-report questionnaires while ToM was assessed using the University of Cape Town Theory of Mind Battery. ASD diagnoses were confirmed using the Autism Diagnostic Observation Schedule, Second Edition (ADOS2). Results showed that while both the ASD group and the neurotypical group reported significantly more Authoritative parenting than the other two styles (Authoritarian and Permissive), there was also more of the less positive parenting styles reported in the ASD group. Furthermore, none of the three parenting styles in question were significant predictors of Theory of Mind. The results further indicated that the ASD group reported less secure attachment, and also more insecure attachment (Ambivalent and Avoidant) than the neurotypical group. Attachment classification, specifically insecure attachment, showed to be a significant predictor of Theory of Mind. Associations between parenting style and attachment showed different patterns in the ASD sample compared to the neurotypical sample. Results, limitations, and futher directions were also discussed.